Neuropsychological aspects for evaluating learning disabilities. - Semrud-Clikeman M (Communication Disorders Quarterly)
This review surveys the empirical literature for assessments of learning problems in children from a neuropsychological perspective. An evaluation of children with learning problems must consider measures of working memory, attention, executive function, and comprehension (listening and written), particularly for children who do not respond to intervention. These constructs must be tied to intervention techniques, and their connections must be empirically verified. The response-to-intervention (RTI) perspective provides excellent support for the process in young children but is still developing the process for students above the second grade. This review provides information about the existing research on neurobiological correlates of learning disabilities, possible areas for further evaluation, and the link to the RTI movement.